2002
DOI: 10.1074/jbc.m202893200
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed Mutagenesis of the Basic N-terminal Cluster of Pancreatic Bile Salt-dependent Lipase

Abstract: Previous studies have postulated the presence of a heparin-binding site on the bile salt-dependent lipase (BSDL), whereas two bile salt-binding sites regulate the enzyme activity. One of these sites may overlap with the tentative heparin-binding site at the level of an N-terminal basic cluster consisting of positive residues Lys 32 , Lys 56 , Lys 61 , Lys 62 , and Arg 63 . The present study uses specific site-directed mutagenesis to determine the functional significance of this basic cluster. Mutations in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…2) showed that BSDL is present in culture media of 3B and MC9 clone excepted that of control clone C1. However, clone 3B expressed and secreted two glycoforms of the wild-type BSDL migrating at 74 and 70 kDa, respectively (11,14). These two glycoforms are also detected in rat pancreatic AR4 -2J cells expressing BSDL (19).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2) showed that BSDL is present in culture media of 3B and MC9 clone excepted that of control clone C1. However, clone 3B expressed and secreted two glycoforms of the wild-type BSDL migrating at 74 and 70 kDa, respectively (11,14). These two glycoforms are also detected in rat pancreatic AR4 -2J cells expressing BSDL (19).…”
Section: Resultsmentioning
confidence: 99%
“…However, wild-type BSDL activity on 4-NPC largely increased in the presence of 4 mM NaTC, whereas NaTC (125 M) or NaTDC (125 M or 4 mM) activates BSDL to a relatively lesser extent (ϳ50%) compared with NaTC. The activity of mutagenized R423A/K429I/R454A/ R458A/K462I BSDL cannot be activated by NaTC or by NaTDC when used at lower (125 M) or higher (4 mM) concentrations than their respective critical micellar concentration (CMC) determined under BSDL assay conditions that were 1.4 and 0.5 mM for NaTC and NaTDC, respectively (11).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations